İran’da Osmanlı Kaza İdaresinin Kurulması ve Kadı Tevcîhatı (1723-1735) - Kuru, Levent (FSM Vakıf Üniversitesi, 2020)
18. yüzyılın başından itibaren Safevi hanedanından memnun olmayan grupların başlattıkları isyanlar İran coğrafyasını istikrarsızlığa sürükledi. Bu durumdan yararlanan Osmanlı Hükümeti Haziran 1723’te İran seferini başlatarak üç koldan Safevi topraklarına girdi. Yapılan fetihlerle birlikte Haziran 1735’e kadar İran sahasında kaldılar. Osmanlı yönetimi İran’da fethettiği yerleri zaman kaybetmeden kendi idari sistemine dâhil etmek için çalışmalar yapmıştır. Bu makalede; XVIII. yüzyılın ilk yarısında İran’da Osmanlı kaza idaresinin kurulma çalışmaları, kazaların statüleri, sistem tesis edilirken ortaya çıkan aksaklıklar, bunlara karşı alınan tedbirler ve kurulan kazalara yapılan tevcih işlemleri ele alınacaktır.

From the beginning of the 18th century, riots initiated by groups that were dissatisfied with the Safavid dynasty caused the Iran’s geography to become unstable. The Ottoman Government, who benefited from this situation, started the Iran expedition in June 1723 and entered Safavid territory from three sides. With the conquests, the Ottomans remained in the Iranian area until June 1735. The Ottoman administration made an endeavour to incorporate the places conquered in Iran into its administrative system without delay. In this article, the establishment of the Ottoman district administration in Iran in the first half of the XVIII. century, the status of districts, problems that occurred during the establishment of the system as well as the measures taken in this regard and the procedures for assignments to the districts established in Iran will be discussed.
Establishment of District Ottoman Administration in Iran and Kadi Assignments (1723-1735)
Keywords: Osmanlı; Safevi; İran; Kaza; Anadolu Kazaskerliği; Ottoman; Safavid; Iran; District; Anatolian Kadi’asker